Influences of Residual Water in High Specific Surface Area Carbon on the Capacitor Performances in an Organic Electrolyte Solution. (10th July 2016) - Morita, Masayuki; Noguchi, Yuya; Tokita, Masahiro; Yoshimoto, Nobuko; Fujii, Kenta; Utsunomiya, Takashi
Highlights: Influences of residual water in activated carbon were examined on capacitor performances. The residual water does not affect much on the capacitor behavior under mild conditions. More water in the carbon deteriorates the performance under high rate cycling. High-voltage floating accelerates the degradation of the electrode containing more water. The capacitance loss by cycling is caused by the increase in the interfacial resistance. Abstract: Charge-discharge behavior of an electric double-layer capacitor consisting of conventional activated carbon electrodes with an organic electrolyte solution have been investigated as a function of the amount of residual water in the carbon. The water contents in the carbon powder were estimated by the titration of the released water in acetonitrile solvent by assuming adsorption-distribution equilibrium between the solid carbon and the organic solvent phases. The residual water in the carbon much influenced the capacitor performances, especially in the cycling with high-rate or high-voltage floating. The constant-current cycling at higher current rates decreased the specific capacitance and increased the internal resistance for the electrodes containing higher amounts of residual water. The degradation behavior was more significantly observed for the electrode containing more water when the charge-discharge cycling was accompanied by high-voltage floating.